Revealing the factors determining the selectivity of guaiacol HDO reaction pathways using ZrP-supported Co and Ni catalysts - Han, Geun-Ho; Lee, Min Woo; Park, Soohyung; Kim, Ho Joong; Ahn, Jae-Pyoung; Seo, Myung-gi; Lee, Kwan-Young (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2019)
Guaiacol, a primary chemical derived from lignin, is still an attractive candidate as a cyclical carbon source in the petroleum industry. This work newly introduced Co/ZrP and Ni/ZrP catalysts and examined their activity for guaiacol hydrodeoxygenation (HDO) in a batch reactor at 573 K and under 70 bar of H-2. Their catalytic, surface and textural properties were investigated by XRD, N-2 adsorption-desorption, H-2-TPR, H-2-TPD, NH3-TPD, HAADF-STEM and H-2 -chemisorption. In addition, the overall reaction pathways of guaiacol to cyclohexane on Co/ZrP and Ni/ZrP were proposed. Guaiacol was converted to cyclohexane through two different pathways via two major intermediates: phenol (demethoxylation, PHE route) and 2-methoxycyclohexanol (hydrogenation, 2-M route). Co/ZrP preferred the PHE-route, while Ni/ZrP dominantly favored the 2-M-route, which resulted in a high cyclohexane yield when using Co/ZrP (76%). In this study, an 'intrinsic H-2 supply' was determined to be the main factor for selecting the reaction pathway. Co/ZrP, with a low intrinsic H-2 supply capacity, promoted a less H-2-consuming pathway (PHE route), and Ni/ZrP, with a high intrinsic H-2 supply, favored the more H-2-consuming 2-M route. Likewise, lowering the H-2 pressure (from 70 to 40 bar) could promote the PHE route and increase cyclohexane production (80%). However, the opposite trend was observed when the reaction temperature was reduced from 573 K to 5231<. For both Co/ZrP and Ni/ZrP catalysts, the production of PHE significantly decreased, while the same yield of 2-M was almost maintained. Thus, the pathway preference of Co/ZrP was reversed to the 2-M-route. Guaiacol HDO pathway preference over Co/ZrP and Ni/ZrP catalysts was characterized and the reaction conditions were investigated in this study, which could provide a guideline for effective ways to produce desired chemicals from guaiacol using Co/ZrP and Ni/ZrP. (C) 2019 Elsevier Inc. All rights reserved.
Keywords: AQUEOUS-PHASE HYDRODEOXYGENATION; SOLVOLYSED LIGNOCELLULOSIC BIOMASS; MODEL-COMPOUND; BIO-OIL; ZIRCONIUM-PHOSPHATE; SULFIDED COMO/GAMMA-AL2O3; PHENOL HYDRODEOXYGENATION; ELECTRIC VEHICLE; LIGNIN; METAL